The Use of Body Language and Non-verbal Communication in Teaching Grammar - Musa, Abdelmjeed; Mohamed, Tawasol (JOURNAL OF ADVANCES IN LINGUISTICS, 2025)
This is an extract from a Ph.D. thesis entitled “The Impact of Non-verbal Communication in Conveying Meaning in English for EFL Classrooms”. It aims solely at investigating the use of non-verbal communication and body language and their fundamental roles in facilitating English grammar to ESL students. It sheds light on the very significant points that non-verbal communication acts in making English grammar lessons easy and smooth for both teachers and students. The study follows the quantitative and the descriptive methods and the data have been analyzed statistically using the SPSS program. It hypothesizes that (Non-verbal communication helps EFL teachers to convey the grammar meaning).Five statements have been emerged out of the hypothesis to form the questionnaire (see table 2). After analyzing the data, the results reveal that the average of most agreeable statements are 61% and 27.6 strongly agree and agree consecutively. While the least percentages are 8% and 1.8% which are undecided and disagree with 0% of strongly disagree. Based on the obtained results, a conclusion can be drawn that the study is consistent and valid.